Peningkatan Pemberdayaan Perempuan Menuju Keluarga Sukinah Melalui Penyuluhan Pengasuhan Anak - Luh Gede Surya Kartika; I Made adi Widnyana; Kadek Aria Prima Dewi PF; Ni Wayan Arini (IAHN Gde Pudja Mataram, 2022)
The concept of the sukinah family is a happy and prosperous family. A mother has a very important role in the formation of a sukinah family, especially in terms of fulfilling children's rights. To support the achievement of the Sukinah family in Indonesia and also to commemorate National Children's Day, community service activities were held in Nyuhtebel Village, Manggis District, Karangasem Regency by Uniersitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar. This activity was aim to provide education to mothers in Nyuhtebel Village about child care. The result of this activity was that the mothers who participated in the activity understood the importance of their role in creating a sukinah family. Participants also understand existing parenting styles and the impact or benefits of each styles. It is hoped that participants can share on the information obtained to other family members after the activity is completed.